A UNDIME e a municipalização do ensino com ênfase ao estado do Paraná, 1986 - 2000 - Pinheiro, José Vanelli (2001)
This work intends to rescue a little of the history of Brazilian education in what concerns the centralization and decentralization of teaching, the definition of competences between the spheres of federal, state and municipal government. The history of UNDIME (Union of Municipal Education Directors) and its participation in the process of municipalization of elementary education is also emphasized. Education in Brazil, since the beginning, has undergone alternating periods of centralization and decentralization, according to political changes. The effective ideas of decentralization started with the 1891 Republican Constitution. The municipalities arose, however they were dependent and weak, the collection processes were centralized and the distribution of resources did not obey strictly technical criteria. Thus, more than half of the Brazilian population remained illiterate at the beginning of the 20th century. In the 1930s and 1940s, the question of expanding public and free education and its competences was already much discussed, and the 1946 Constitution defined the percentages of application of resources by the Union, states and municipalities. The municipalization of education in Brazil only had legal support from 1961, when the Law of Guidelines and Bases (LDB) n °. 4,024 / 61, attributed some charges to education to the municipalities. The military regime that was installed in 1964, very centralized, restricted the progress towards greater decentralization. With the redemocratization of the country in 1985 and the convening of the Constituent Assembly, discussions on the municipalization of elementary education returned. Several organizations and entities linked to education participated in the discussions. In 1986, the UNDIME (Union of Municipal Education Directors) was created, which became a representative entity of the municipalities in the debates on the directions of Brazilian education. by extending the possibility of managing elementary education to municipalities.The history of UNDIME in Brazil and especially in the State of Paraná is closely linked to the history of the municipalization of education and also to the life story of the author of this dissertation. In this state, the author was one of the organizers and the first president of the entity. The good relationship between UNDIME-PR and the Paraná State Department of Education contributed to the accelerated evolution of the process of municipalization of education, with the forecast that in 2004 all primary schools will be under the administration of the municipalities. . Today, in 2001, the municipalities already took over 98% of the schools in the first grades of 1st to 4th grades.